Pengaruh Lingkungan Keluarga terhadap Children Well-Being Anak Usia Dini: Systematic Literature Review - Salma Nur Septiani; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to comprehensively examine the influence of the family environment on early childhood children’s well-being through a Systematic Literature Review (SLR) approach. The study employed an SLR design following the PRISMA guidelines, involving the identification, screening, and analysis of relevant scholarly articles from various academic databases. The inclusion criteria focused on recent studies addressing family environment and early childhood well-being. The findings reveal that the family environment plays a crucial role in shaping children’s well- being, influenced by factors such as family interaction quality, parenting styles, parental involvement, family-based interventions, and modern environmental factors including digital technology use. The study further identifies social-emotional development as a key mediating mechanism linking family environment and children’s well-being. In addition, early family-based interventions are found to be more effective and sustainable compared to interventions implemented at later developmental stages. The novelty of this study lies in integrating multiple dimensions of the family environment into a comprehensive analytical framework and emphasizing social-emotional development as a central mediating variable. This study contributes to enriching the theoretical discourse on children’s well-being and provides practical implications for developing parenting programs, family-based interventions, and early childhood education policies